Attitudes Towards Problem‐Based Learning of Faculty Members at 12 U.S. Medical and Dental Schools: A Comparative Study. Issue 2 (1st February 2018) - Abdelkarim, Ahmad; Schween, Dorothy; Ford, Timothy
Abstract : Problem‐based learning (PBL) is a teaching method used in medical and dental education to promote students' problem‐solving skills. It may also be a viable tool for interprofessional education in which medical and dental students learn together, collaborate, and learn about, from, and with each other. The aim of this study was to compare medical and dental faculty members' attitudes about and perceptions of PBL at 12 U.S. medical and dental schools known to use PBL. In 2015, 111 medical and 132 dental faculty members (combined n=243) from six medical and six dental schools completed a survey containing ten statements and an open comment section. The response rate was 42% of those who received the survey. In the results, the medical faculty participants showed significantly higher enthusiasm for and agreement with PBL benefits than did the dental faculty participants (p˂0.05). The two groups agreed that PBL should be used to supplement conventional teaching (p>0.05). There were no opposite attitudes or contrasts found between the two groups with regards to PBL. The strongest themes expressed by both groups were that PBL should not be used as the sole method of instruction and that students needed a solid foundation in the subject prior to engaging in PBL.